2023
DOI: 10.1038/s41598-023-32738-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimized multiherbal combination and in vivo anti-skin aging potential: a randomized double blind placebo controlled study

Abstract: The present study aimed to optimize a multi-herbal combination exerting the greatest antioxidant property using statistical method for anti-skin aging application as well as to elucidate its in vivo safety and anti-skin aging potential. The multi-herbal combination was optimized using a two-level, full factorial approach by exploring the correlation between the concentrations (0–3%w/v) of three extracts from Centella asiatica (CA), Momordica cochinchinensis (MA), Phyllanthus emblica (EM). An anti-skin aging em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…(All data are shown as mean ± SD of at least three independent experiments. * P < 0.05; ** P < 0.01) vironmental stimulation [38]. One obvious physical sign of skin senescence is the degradation of the ECM.…”
Section: Resultsmentioning
confidence: 98%
“…(All data are shown as mean ± SD of at least three independent experiments. * P < 0.05; ** P < 0.01) vironmental stimulation [38]. One obvious physical sign of skin senescence is the degradation of the ECM.…”
Section: Resultsmentioning
confidence: 98%
“…Se atribuye este efecto a las propiedades antioxidantes de EM de disminuir los ROS, por lo tanto, impedir la formación de metaloproteinasas, en consecuencia, menor daño al colágeno y elastina; también tiene propiedades antirosinasa, involucrada en la aparición de manchas (lentigos solares) debido a su acción en la melanogénesis, por otro lado, CA promueve el inicio de la producción de colágeno especialmente el tipo I pues activa la vía SMAD/factor de crecimiento beta. (16) En la extracción de componentes polifenólicos, de la semilla del mango y su efecto como posible alternativa al tratamiento, eliminan ROS, reduce la actividad de la tirosinasa; anti-metaloproteinasas; inhibe el óxido nítrico, IL 6 e IL 8. Sin embargo, estos resultados solo son in vitro y no se puede aun saber la efectividad como tratamiento en la piel humana.…”
Section: Tratamientounclassified
“…In some studies, plants have been shown to exert notable in vivo anti-aging properties. According to the literature, skin parameters associated with skin aging, such as skin hydration (measured with a corneometer and tewameter), skin elasticity (measured with a cutometer and elastometer) or facial wrinkles (measured with a skin visiometer and camera for skin analysis) have been evaluated following the application of cosmetic formulations based on various plant extracts, alone or in combination [119,[150][151][152]. Table 3 cites research from the last five years on selected plant species and their extracts with potential uses as agents preventing and slowing down skin aging.…”
Section: Plants As Anti-aging Agentsmentioning
confidence: 99%